Exploring Stem Cell Therapy for Burn Wounds: A Review of Current Variations and Advances - Soya Loviana Hasibuan; Syamsul Rizal; Mirnasari Amirsyah; Dewi Fibrini (Journal of Comprehensive Science, 2026)
Burn wounds causes disabilities that lower quality of life and productivity, and can even result in death. Therefore, a promising therapy that may accelerate the healing process of burn wounds and prevent disabilities is currently being developed. The sources from international journals obtained through computer-based literature searches by PubMed, ScienceDirect, Springer Link, and Google Scholar. The focus is on publications from the past five years (2019-2024) using keywords such as "Stem cell," "Burn wound healing," "secretome dental pulp," "Umbilical cord stem cell," "Embryonic stem cells," "Hair follicle derived stem cell," "Adipose tissue derived stem cell," and "Bone marrow derived stem cell." Additionally, academic works (theses) were searched in the Prima University Medan campus library, resulting in a total of 38 articles and one thesis. Four articles and one thesis were then selected based on the required information. The selected articles were analyzed through activities including collection, evaluation, and research development, focusing on comparisons between different types of stem cells. Stem cell therapy for burn wounds is accelerating healing by helping reduce systemic inflammatory responses, enhancing the regulation of anti-inflammatory cytokines, reducing pro-inflammatory cytokines, promoting angiogenesis, modulating the functions of T cells, B cells, and monocytes or macrophages. Adipose tissue derived stem cells are claimed to be the best stem cell therapy, but in practical application, Hair follicle-derived stem cells are the easiest to use. In terms of maximum healing percentage, Human Secretome Dental Pulp stem cells have great potentia stem cell therapy due to their double healing concept